The Effect of Inter-tribal Post Election Violence Conflict Trauma on Academic Performance among Secondary School Students in Mt. Elgon District, Kenya - Nasongo, B. M; Muola, James Muthee (International Association of African Researchers, 2011)
Inter-tribal conflict in Kenya has persisted for a long time and intensifies during elections. The inter-tribal conflict in 2007-2008 in Mt. Elgon District was apparently over land dispute between the Soy and Ndorobo clans of the Sabaot tribe. This research aimed at establishing the effect of trauma as a result of inter-ethnic conflicts on academic performance among secondary school students in Mt Elgon District, Kenya. The ex-post facto research design was used. Two questionnaires, one for students and another one for teacher-counsellors were used to collect data. The sample of study comprised of 90 randomly selected students and six teacher-counsellors from six purposively sampled schools from a population of 22 secondary schools. Five (83%) out of the six sampled schools registered a negative performance index in the Kenya Certificate of Secondary Examination (KCSE) for the year 2008. In addition, 98% of the respondents recorded a negative performance index in their internal examination results. More girls (70%) registered a negative drop than boys (32%). The findings showed that 70 (78%) of the student-respondents sought counseling services while 20 (22%) did not. It was recommended that trauma counseling should be entrenched in the school system
Keywords: Trauma; Academic performance; Gender and violence